Developing a scale for quality self assessment in pre-hospital emergency services - Mozafari, Mosayeb; Abedsaeedi, Zhila; Amini, Yasamin; Vafaee, Reza (Archives of Advances in Biosciences, 2013)
Establishing of total quality management in any organization including emergency medical services need to an appropriate tool to help developing, implementing and evaluating of quality programs. The objective of this study was to develop a valid and reliable tool for self assessing enabler criteria of Iran EMS centers according to European Foundation for Quality Management (EFQM) model.The study was conducted using the Delphi method, and 43 participants as panelists were enrolled in 3 round modified Delphi technique. Initially, a rating scale was developed in response to main question of study; which items should be contained in self assessing tool of quality in Iran EMS area? This scale was judged by 5 experts primarily, and after some modification was entered in Delphi process. The comments of panelist were collected by E Mail and final scale was developed in the end of 3th rand.Pre-hospital Emergency Self assessing Rating Scale (PHESARS), Was main result of this study that developed in 190 items in 5 enabler criteria according to EFQM model including; Leadership (52), Policy & Strategy (21), staff (41), Resources& partnership (36) and Processes (40).Self assessing scale was developed by TQM and excellence perspective and because of experts' consensus in developing it, has content validity and can be used in self assessing of pre-hospital area and determining improvement opportunity and, can leads the Iran EMS centers to total quality management and organizational excellence.